(untitled) (Journal Of Educational and Psychological Researches, 2022)
The main aim of this research is to: 1) identify the Transformational Leadership of the Managers of higher School in ALkut district and its relationship with organizational Loyalty. 2) Clarify the relationship between Transformational Leadership and organizational Loyalty. Regarding the research methodology, the researcher used the descriptive method because it meets this research. The two research tools were a questionnaire and the statistical program (spss). The results revealed that there is a strong positive relationship between Transformational Leadership and organizational Loyalty, which means that when the managers have a Transformational Leadership leads to having organizational loyalty.